Lumbosacral Nerve Root Avulsions: MR Imaging Demonstration of Acute Abnormalities - Sasaka, K.K.; Phisitkul, P.; Boyd, J.L.; Marsh, J.L.; El-Khoury, G.Y. (American Journal of Neuroradiology, 2006)
SUMMARY: Most of the previously reported lumbosacral nerve root avulsions presented with pseudomeningoceles at the time of delayed initial imaging. We report a case of traumatic lumbosacral nerve root injury associated with an isolated femur fracture and demonstrate the evolution of pseudomeningoceles following nerve root avulsions and edema in the perineural fat identified on the initial MR imaging.